2017
DOI: 10.1002/anie.201611067
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Asymmetric Synthesis of Disubstituted Allenes by Coupling of Flow‐Generated Diazo Compounds and Propargylated Amines

Abstract: We report herein the asymmetric coupling of flow‐generated unstabilized diazo compounds and propargylated amine derivatives, using a new pyridinebis(imidazoline) ligand, a copper catalyst and base. The reaction proceeds rapidly, generating chiral allenes in 10–20 minutes with high enantioselectivity (89–98 % de/ee), moderate yields and a wide functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 87 publications
1
54
0
1
Order By: Relevance
“…Firstly, when using 1,2-di- p -tolyldisulfane and TMSCN as the substrates, 2a was generated in 78% yield (Scheme 2, eqn (1)), which indicated that thiocyanate could be generated in a good yield under the standard conditions with TMSCN as the cyano source. To validate that the copper carbene species would promote the S–CN bond cleavage, we next mixed (1-diazoethyl) benzene 18 and 2a in the reaction system without a base. However, 3aa was generated in only 21% yield (Scheme 2, eqn (2a)), which might be due to the instability of the diazo compound at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, when using 1,2-di- p -tolyldisulfane and TMSCN as the substrates, 2a was generated in 78% yield (Scheme 2, eqn (1)), which indicated that thiocyanate could be generated in a good yield under the standard conditions with TMSCN as the cyano source. To validate that the copper carbene species would promote the S–CN bond cleavage, we next mixed (1-diazoethyl) benzene 18 and 2a in the reaction system without a base. However, 3aa was generated in only 21% yield (Scheme 2, eqn (2a)), which might be due to the instability of the diazo compound at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the authors reported on aliphatic substrates, propargylic alcohols, amines and two examples of the late stage functionalization of a steroid (norethindrone) and a propargylated alkaloid (quinine) ( 15 c , 15 d , Scheme b) . This concept was then extended in an enantioselective reaction using a chiral copper complex and propargylic amines providing a convenient access to homo allenic amines ( 17 ) with high enantiocontrol …”
Section: Oxidation Of Hydrazonesmentioning
confidence: 99%
“…[31] This concept was then extended in an enantioselectiver eactionu sing ac hiral copper complex and propargylic amines providing ac onvenient access to homo allenic amines (17)w ith high enantiocontrol. [32] Shortly after their seminalp ublication, Leya nd co-workers furthere xploredt his concept in the metal-free cyclopropanation of donor diazo compounds with dehydro amino acid derivative(19)a nd ethylidene malonates and were able to obtain ar ange of different ester-substituted cyclopropanes (20,Scheme7). Furthermore, Ley and co-workerse stablished af low protocol, which comprises the generationo ft he diazo compoundi nf low andt he consecutive cyclopropanation in a second flow reactor.…”
Section: Oxidation Of Hydrazonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Following their previous synthesis of di ‐, and tri‐ substituted allene through the coupling of non‐stabilized flow‐generated diazo compounds with terminal alkynes, Ley and coworkers in 2017 reported catalytic asymmetric reaction using flow‐generated diazo compounds with propargylated amine derivatives in the presence of chiral pyridinebis(imidazoline) ligand/Cu(I) catalyst and base (Figure ) . The reaction proceeds rapidly, generating chiral allenes in 10–20 minutes with high enantioselectivities and a wide functional group tolerance.…”
Section: Asymmetric Allene Synthesis Through Cu(i)‐catalyzed Couplingmentioning
confidence: 99%